Can we define and characterize the aging lower urinary tract?—ICI‐RS 2015. Issue 4 (April 2017) - Vahabi, Bahareh; Wagg, Adrian S.; Rosier, Peter F.W.M.; Rademakers, Kevin L.J.; Denys, Marie‐Astrid; Pontari, Michel; Lovick, Thelma; Valentini, Francoise A.; Nelson, Pierre P.; Andersson, Karl‐Erik; Fry, Christopher H.
Abstract : The prevalence of lower urinary tract (LUT) symptoms increases with age but the etiology is unknown. This article aims to identify research directions that clarify the basis of this association. The initial question is whether biological age is the variable of interest or a time‐dependent accumulation of factors that impact on LUT function at rates that differ between individuals. In particular, the accumulation of conditions or agents due to inflammatory states or tissue ischemia is important. Much of the above has been concerned with changes to bladder function and morphology. However, the outflow tract function is also affected, in particular changes to the function of external sphincter skeletal muscle and associated sacral motor nerve control. Nocturia is a cardinal symptom of LUT dysfunction and is more prevalent with aging. Urine production is determined by diurnal changes to the production of certain hormones as well as arterial blood pressure and such diurnal rhythms are blunted in subjects with nocturia, but the causal links remain to be elucidated. Changes to the central nervous control of LUT function with age are also increasingly recognized, whether in mid‐brain/brainstem regions that directly affect LUT function or in higher centers that determine psycho‐social and emotional factors impinging on the LUT. In particular, the linkage between increasing white matter hyperintensities and LUT dysfunction during aging is recognized but not understood. Overall, a more rational approach is being developed to link LUT dysfunction with factors that accumulate with age, however, the precise causal pathways remain to be characterized. Neurourol. Urodynam. 36:854–858, 2017 . © 2017 Wiley Periodicals, Inc.